Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006611.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone-based interventions for smoking cessation

Abstract: The current evidence shows no effect of mobile phone-based smoking cessation interventions on long-term outcome. While short-term results are positive, more rigorous studies of the long-term effects of mobile phone-based smoking cessation interventions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(95 citation statements)
references
References 27 publications
6
88
0
1
Order By: Relevance
“…The remaining reports of mobile technologies for smoking cessation were a range of studies including descriptions of design and development; reports of feasibility, acceptability, and usability data; uncontrolled trials; and various systematic reviews. For completeness, 2 Cochrane meta-analyses of this area 140,141 are included in the table.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
See 1 more Smart Citation
“…The remaining reports of mobile technologies for smoking cessation were a range of studies including descriptions of design and development; reports of feasibility, acceptability, and usability data; uncontrolled trials; and various systematic reviews. For completeness, 2 Cochrane meta-analyses of this area 140,141 are included in the table.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…Cochrane Meta-Analysis Controlled studies of mobile phone programs for smoking cessation have been summarized in a Cochrane meta-analysis 140 and update. 141 The details of studies reviewed in these 2 meta-analyses are listed in Table 4.…”
mentioning
confidence: 99%
“…74,75 Recent systematic reviews have shown that text messages can successfully change behaviour. [76][77][78] This type of intervention is particularly well suited to middle-aged men because their ownership of mobile phones is high. 79 The behaviour change strategy was based on the Health Action Process Approach (HAPA).…”
Section: The Text Messagesmentioning
confidence: 99%
“…A plethora of recent systematic reviews provide further support for the short-term efficacy of text message-delivered interventions across different health behaviours among different age groups and populations (Head et al, 2013;Jones et al, 2014;Mason et al, 2014;Poorman et al, 2014;Saffari et al, 2014;Whittaker et al, 2009).…”
Section: Initial Behaviour Change Interventions Delivered Via Text Mementioning
confidence: 99%
“…This evidence gap on reporting of maintenance outcomes is mirrored in the broader adult population literature Text messaging is a potential cost-effective and broad reach modality to deliver the extended contact interventions that are needed to promote maintenance of behaviour change. There is evidence to support the efficacy of using text messaging to deliver shortterm health behaviour change interventions Maddison et al, 2014;Spring et al, 2012;Whittaker et al, 2009), and emerging evidence to support the use of this modality to deliver extended contact interventions ). However, reviews exploring text message-delivered interventions report a focus on adolescents (Lau et al, 2011) and younger adults (Fjeldsoe et al, 2009;Spring et al, 2012).…”
Section: Physical Activity And/or Dietary Behaviour Change Interventimentioning
confidence: 99%